Health-Related Quality of Life in Italian Adolescents During Covid-19 Outbreak - Mastorci, Francesca; Piaggi, Paolo; Doveri, Cristina; Trivellini, Gabriele; Casu, Anselmo; Pozzi, Marta; Vassalle, Cristina; Pingitore, Alessandro (Frontiers in Pediatrics, 2021)
Coronavirus disease 2019 (COVID-19) outbreak represented an experience of social isolation potentially leading to changes in the health quality of life. The aim of this study is to investigate the health-related quality of life during quarantine in early adolescents. Data were collected from 1,289 adolescents (mean age, 12.5; male, 622), at the beginning of the school year (September 2019, Standard Condition, SC) as part of the AVATAR project and during Phase 1 of the Italian lockdown (mid-late April 2020) (COVID-19 Quarantine, CQ) using an online questionnaire. In the CQ period, with respect to SC, adolescents showed lower perception in the dimensions, such as psychological (p = 0.001), physical well-being (p = 0.001), mood/emotion (p = 0.008), autonomy (p = 0.001), and financial resources (p = 0.018). Relationship with the family (p = 0.021) and peers (p = 0.001), as well as the perception of bullying (p = 0.001) were reduced. In lifestyle, adolescents developed higher adherence to the Mediterranean diet (p = 0.001). Adolescents living in the village had greater reduction in both autonomy (p = 0.002) and peer relationships (p = 0.002). Moreover, the perception of physical well-being was lower in those living in the city instead of those living in the countryside (p = 0.03), in an apartment instead of a detached house (p = 0.002), and in those who did not have green space (p = 0.001). Gender effect emerged for the psychological (p = 0.007) and physical well-being (p = 0.001), mood/emotion (p = 0.001), and self-perception (p = 0.001). The study showed that health-related quality of life during quarantine changed in its psychosocial dimensions, from mood and self-esteem to social relationships, helping to define the educational policies at multiple points in the promotion process of health.